IMPLEMENTATION OF THE AHP METHOD ON DECISION SUPPORT SYSTEM FOR SELECTING THE BEST RICE SEEDLINGS IN MADANG SUKU 1 SUB-DISTRICT - Utami, Putri Ela Citra; Ruskan, Endang Lestari (Jurnal Sistem Informasi dan Ilmu Komputer, 2024)
Rice is one of the most widely grown staples in most rural areas in Indonesia. East OKU Regency is the Regency with the second largest rice production in South Sumatra Province, Madang Suku 1 District is one of the Districts in East OKU Regency and is the center of rice production. However, many farmers in Madang Suku 1 do not know the quality of rice seeds that are by the criteria that are suitable for the village where the farm is, resulting in unsatisfactory yields for farmers, which has an impact on the welfare of rice farmers. Therefore, to help overcome the problems that occur, a system is needed that can help farmers in choosing the best rice seeds that suit the conditions of the area. This decision support system uses the AHP method, this method can make decisions effectively with complex and then simplified in a hierarchical arrangement. In addition, this method can also take into account the level of consistency and inconsistency in the assessment carried out by comparing existing factors or criteria. This research resulted in the ranking of rice recommendations for Madang Sub-district Tribe 1 which is 1.855 obtained by MR, Inpari 42 = 1.470, Ciherang = 1.119, Inpari 32 = 1.000, and Ciliwung with a value of 0.558. Keywords: Decision Support Systems; Analytical Hierarchy Process; Rice Seedlings;